Development characteristics of preschool aged girls from different urban areas - Darko Stojanović; Nikola Stojanović; Ratomir Đurašković (University of Banja Luka, Faculty of physical education and sport, 2016)
Human growth and development are under the influence of both genetic and environmental factors. Longitudinal and transversal dimensions of skeleton are, to a large extent, genetically determined contrary to circular dimensions, body weight and skin fold. The aim of this research was to determine developmental differences between the girls from Vranje and Užice. This research was conducted in kindergartens of Vranje and Užice. The sample comprised 136 girls, 72 of whom were 5 (+ eight months) years of age from Užice, and 64 of whom were 5 (+ seven months) years of age from Vranje. We used standardized instruments to measure the anthropometric characteristics, according to the methodology recommended by the International Biological Program (Weiner & Lourie, 1981). The average height of the girls from Vranje is 118, 6±5, 37 cm, and of the girls from Užice 119, 4±5, 46 cm. The girls from Užice were taller than those from Vranje, but the difference in height is not statistically significant. The results have shown that there is statistically significant difference in leg length. The average leg length of the girls from Vranje is 63,2±4,55cm, and those from Užice 64,7±3,96 cm. The girls from Vranje have greater pelvic width than the girls from Užice, which is statistically significant. We have not observed statistically significant differences concerning other measured anthropometric variables.